Analysis Toward the Role of Panca Bhuana Tunggal Bhakti in the Resolution of Interreligious Marriages in the Bali Community In Konawe District, Indonesia - Muhamad Fandi; Jabalnur; Idaman idaman (Journal of Law, Social Science and Management, 2025)
Background: Marriage is generally a straightforward matter when both individuals share the same religion. However, it becomes complex when couples belong to different faiths. In such cases, religious and customary differences may hinder marriage procedures and necessitate prolonged resolution involving religious and traditional leaders. Objective: This study aims to analyze the role of the Panca Bhuana Tunggal Bhakti Customary Institution in resolving interfaith marriages within the Balinese community in Konawe Regency. Method: This empirical legal research employs legislative, case-based, conceptual, and historical approaches to examine legal and customary practices related to interfaith marriage. Results: In Hinduism, marriage (wiwaha) is considered sacred and permissible only between individuals of the same faith. Article 2(1) of Law No. 1 of 1974 affirms that marriage is valid only if conducted according to religious norms. The Sudhiwadani ceremony serves to facilitate religious conversion for non-Hindu partners, thereby legitimizing the marriage both religiously and legally. The Panca Bhuana Tunggal Bhakti Institution plays a crucial role in maintaining social harmony by organizing and legitimizing the Sudhiwadani ritual, thereby ensuring the legal and spiritual validity of interfaith marriages. Conclusion: The Sudhiwadani ceremony, rooted in the concept of Atmanastuti, highlights spiritual awareness, self-contentment, and legal deliberation in Hinduism. This ritual fosters harmonious family life and upholds tolerance, while also providing legal certainty and social recognition for interfaith marriages. Keywords: Customary Institution, Panca Bhuana Tunggal Bhakti, Interfaith Marriage, Sudhiwadani, Hindu Law